Corrosive injury of upper gastrointestinal tract and it outcome - Baluni, Uday Shankar; Mistry, Tejas; Kothari, Ankur; Patel, Tejas (International Surgery Journal, 2017)
Background: Corrosive gastrointestinal tract injuries are a source of considerable morbidity all over the world and differ in their presentations. Methods: In the present work, study was done on 41 patients with history of acute corrosive injury with a period of 24 hours of ingestion and analysis on the parameters of age, sex, mode of ingestion, nature of corrosive, clinical symptoms. Further UGI scopy was also done within 24 to 48 hours of admissions. Results: With the study it was found that, the incidence of corrosive ingestion was reducing as the age was increasing and among all patients 27 were females and only 14 were males. The most common cause of corrosive ingestion was suicidal found in 30 cases and only 11 were accidental and most common nature of corrosive used was acid. 2 patients get expired during the initial resuscitation. On GI scopy, 18 have grade 1, 12 have grade 0, 4 have grade 2 and 7 have grade 3 according to Zargar classification. Initially 35 patients were given conservative treatment and 4 cases were treated surgically by feeding jejunostomy. On follow up 31 were advised for conservative management and 7 required surgical management, out of which esophageal dilatation was done in 2 cases, esophageactomy in 2 cases and gastrojejunostomy was done in cases and one case get expired. Conclusions: Corrosive ingestion patient are managed on the basis of UGI scopic grading.